Promoting Students’ Scientific Thinking through Design-Oriented Activities in a Modern Educational Environment - Nataliia Bondarenko; Oksana Pasko; Olha Shpak; Volodymyr Tymenko; Andrii Kudra (ASEAN Journal of Educational Research and Technology, 2026)
This study examined the effectiveness of design-oriented activities in promoting students’ scientific thinking in a modern educational environment. A quasi-experimental pre-test–post-test design was applied to 60 first-year bachelor’s students in Design, divided into experimental and control groups. The experimental group completed the “Design Thinking and Scientific Research” course, while the control group followed the standard curriculum. Data were collected using a scientific thinking diagnostic tool, a design thinking engagement questionnaire, and expert assessment of design projects. The results showed significant improvement in analytical skills, criticality, systematicity, hypotheticality, and evidence-based reasoning among the experimental group. The findings indicate that design thinking can strengthen scientific thinking in higher education.